The role of early life factors in the development of ethnic differences in growth and overweight in preschool children: a prospective birth cohort - van Rossem, Lenie (BMC Public Health, 2014)
BACKGROUND: Ethnic differences in childhood and adulthood are known, but ethnic differences in preschool overweight and associated factors are less studied. We assessed ethnic differences in pre-school age overweight, and studied the mediating role of early life factors in this association. Furthermore, we assessed body mass index (BMI) z-score development from birth to age 4 years to study ethnic-specific differences in BMI z-score trajectory. METHODS: We used data on 4581 children participating in a birth cohort who were born between 2002 and 2006 in Rotterdam, the Netherlands. Child’s ethnicity was defined according to country of birth of the parents. Weight and length/height was repeatedly measured between 1 and 45 months of age. Overweight at age 4 years was defined according to cut-off points for BMI from the international obesity task force. We performed logistic regression to obtain independent estimates of the association between ethnicity and preschool-age overweight, and to assess the mediating role of early life risk factors. Mixed models were used to describe BMI-z development for each ethnic group from birth to preschool age. RESULTS: Relative to native Dutch children, non-Dutch children were more likely to be overweight at age 4 years, except for Surinamese-Hindustani children. Socio-demographic factors, parental BMI, and infant weight change in the first 6 months after birth reduced associations. After full adjustment, Turkish (OR: 2.02, 95% CI: 1.34-3.04) and Antillean/Surinamese Creole (OR: 1.78, 95% CI: 1.06-3.02) children were still more likely to be overweight at age 4 years. CONCLUSION: Ethnic differences on the prevalence of overweight in preschool children can be partially explained by maternal educational level, parental overweight and early infant weight change. These may be possible targets to reduce ethnic inequalities in preschool age overweight.